1990
DOI: 10.3168/jds.s0022-0302(90)78919-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Semen Quality in Young and Mature Holstein Bulls Measured by Light Microscopy and Flow Cytometry

Abstract: Random samples of cryopreserved, milk-extended semen, collected from 20 Holstein bulls at about 14 mo of age (young) and again at about 4 yr of age (mature), were evaluated at thawing and during 3-h incubation to compare semen quality of young versus mature bulls. Evaluation by differential interference contrast microscopy showed greater proportions of cytoplasmic droplets in semen from young versus mature bulls. Mature bulls exhibited greater proportions of intact acrosomes in freshly thawed semen than did yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
3
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 13 publications
7
31
3
1
Order By: Relevance
“…That might indicate a higher ‘maturity’ of the semen in older bulls. Karabinus et al. (1990), using conventional tests, concluded that the quality of a randomly selected semen sample from young bulls was generally indicative of the quality of a random sample of their semen as mature bulls.…”
Section: Discussionmentioning
confidence: 99%
“…That might indicate a higher ‘maturity’ of the semen in older bulls. Karabinus et al. (1990), using conventional tests, concluded that the quality of a randomly selected semen sample from young bulls was generally indicative of the quality of a random sample of their semen as mature bulls.…”
Section: Discussionmentioning
confidence: 99%
“…The production of normal spermatozoa changes with age (Chandler et al, 1985;Sta Êlhammar et al, 1989;Karabinus et al, 1990), and pathologies compromising spermatogenesis or the genital function of the sires can arise during the productive lifetime of the bulls at the bull stations. The production of normal spermatozoa changes with age (Chandler et al, 1985;Sta Êlhammar et al, 1989;Karabinus et al, 1990), and pathologies compromising spermatogenesis or the genital function of the sires can arise during the productive lifetime of the bulls at the bull stations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating how aging may affect sperm chromatin integrity in bovine species and the source of the damage are scarce. One study in which semen quality in young bulls and again later in the same mature bulls were evaluated found consistent improvement in semen parameters including sperm DNA integrity, morphology and percentage of intact acrosomes upon aging [9]. In a more recent study, no difference in chromatin integrity as assessed using the sperm chromatin structure assay (SCSA) was found in post-pubertal bulls with mean ages of 13, 18, and 24 months [10].…”
Section: Introductionmentioning
confidence: 99%